Synthesis of adipic aldehyde by n-selective hydroformylation of 4-pentenal - Mormul, Jaroslaw; Mulzer, Michael; Rosendahl, Tobias; Rominger, Frank; Limbach, Michael; Hofmann, Peter (Organometallics, 2015)
Several phosphine and phosphite ligands were tested in the hydroformylation of 4-pentenal to adipic aldehyde, a versatile starting material for industrially very relevant compounds. By varying the ligand structure we were able to increase the selectivity toward adipic aldehyde to >95%. Additionally, two molecular structures of important catalytic intermediates [(bisphosphite)RhH(CO)2] and one structure of a previously unknown catalyst decomposition product were obtained.